Les banques d’hier et d’aujourd’hui : la pierre angulaire du système financier canadien - Bélanger, Michel (Assurances)

(untitled) (HEC Montréal, 1982)
We should like to extend heart-felt thanks to Mr. Michel Bélanger whose article presents a vivid portrayal of the Canadian banking system. The author, President and Chief Executive Officer of the National Bank of Canada, traces the evolution of Canadian banking from its early days, to the 1930's and to modern times, outlining the wide spectrum of services and well-structured branches currently offered bank clients. Mr. Bélanger further expounds upon the development of the chartered bank, its competitors, the solid footing it has secured itself and what it has come to symbolize both at home and on international money markets: a hallmark of economic and social efficiency and leadership.